Potential benefits of GLP-1 analogues and metformin in patients with osteoarthritis - Skowronek, Anna; Piekarska, Martyna; Dąbek, Katarzyna; Ochwat, Michał; Sudoł, Maria; Mierzwa, Gabriela; Kajtel, Aleksandra; Skowronek, Tomasz (Journal of Education, Health and Sport, 2025)
Introduction and purpose Osteoarthritis (OA) is the most prevalent chronic joint disorder. It is the primary cause of chronic pain. Known risk factors for OA include obesity and type 2 diabetes mellitus (T2DM). One of the challenges in managing OA is the absence of disease-modifying treatments. Since obesity is an independent risk factor of OA, the use of medications like GLP-1 analogs and metformin may benefit patients with OA. The purpose of our article was to provide an overview of the findings from studies on the use of the mentioned drugs in OA patients. Materials and methods To write this article, databases such as PubMed and Google Scholar were searched using the following terms: osteoarthritis, glucagon-like peptide-1 (GLP-1), obesity, anti-obesity medications. Description of the state of knowledge Research on the effects of GLP-1 analogs in OA patients has yielded inconclusive results. Some studies showed that semaglutide provided benefits in reducing knee osteoarthritis symptoms in obese, nondiabetic patients. For those with knee OA and T2DM, GLP-1 receptor agonists lowered body weight and pain intensity. Furthermore, patients treated with GLP-1 receptor agonists have a reduced risk of knee surgery and lower cartilage loss velocity. Patients receiving semaglutide who underwent arthroplasty procedures experienced lower risks of prosthetic infections and hospital readmissions. The use of metformin was associated with reduced rates of joint replacement surgery. Conclusions GLP-1-based therapies and metformin, due to their pleiotropic effects, may provide advantages by alleviating joint inflammation and facilitating weight loss in OA patients. Additional research is required to validate these outcomes and identify the most effective treatment approaches for managing OA.